Canine Oral Papillomatosis - Treatment with Association of Azithromycin and Meloxicam - de Melo, Cristiano Barros; Jantorno, Gustavo Machado; de Castro, Márcio Botelho; Mendes Lima, Eduardo Maurício; Bastianetto, Eduardo (Acta Scientiae Veterinariae, 2025)
Background: Canine oral papillomatosis is an infectious disease that usually affects dogs with immune deficiencies, but can eventually regress without treatment. However, this regression without treatment can be time-consuming, taking up to 12 months for complete regression, thus causing more suffering for the dogs and difficulties in the maintenance and hygiene of the animal. Many treatments have been proposed, but most without scientific references, which has often led to frustrating results. The aim of this report is to describe the response to the treatment of one bitch with oral papillomatosis, using Azithromycin associated with Meloxicam. Case: A 6-month-old bitch Pug with skin lesions consistent with canine oral papillomatosis, presenting typical clinical lesions such as exophytic vegetative formations, cauliflower-like lesions and verrucous and hyperkeratotic papules around the mouth and on the internal oral mucosa. The treatment protocol included Azithromycin (10 mg/kg) in combination with Meloxicam (0.1 mg/kg), administered orally every 24 h for 10 days. This therapeutic management protocol was in accordance with the dosage recommendations provided by the manufacturer of the drug approved and commercially available in Brazil. The dog maintained normal appetite and behavior and showed no clinical signs other than the aforementioned lesions. This treatment resulted in complete resolution of the papillomatous lesions. Follow-up monitoring over 12 months showed no recurrence, indicating sustained clinical remission. Discussion: Azithromycin is widely used in Veterinary Medicine to treat various bacterial infections, and it is well tolerated and effective in treating papillomatosis in humans; however, the precise mechanism of its antiviral activity is not fully understood. In the present case, the lesions completely regressed after 10 days of treatment with Azithromycin and Meloxicam. Possibly Meloxicam improved the dog's quality of life during treatment by reducing the discomfort associated with the oral lesions, since other studies have shown that Meloxicam was effective in vitro in reducing cell proliferation, inducing apoptosis and improving the human patient's quality of life by relieving the pain and discomfort caused by the papillomatosis lesions. The combined treatment of Azithromycin and Meloxicam carried out in this case was effective for the rapid resolution of canine oral papillomatosis and without recurrence, indicating sustained clinical remission. Effective treatment is particularly important to avoid a prolonged course of the disease, which can increase the spread of the infection to other dogs. Tumor recurrence after apparently successful treatment is also common and, in addition, the possible malignancy of papillomatous lesions requires prompt and effective treatment. Reducing the incidence of clinical cases of oral papillomatosis in dogs requires strategic management, including appropriate treatment to contain the spread of the virus. Further studies are needed to investigate any specific antiviral activity of these two drugs used on the dog in the present report. Keywords: dog, papillomavirus, wart, disease.